Pemberdayaan Masyarakat dan Kader Posyandu dalam Pengolahan Makanan Pendamping Air Susu Ibu bagi Bayi Usia 6-24 Bulan : Pemberdayaan Masyarakat dan Kader Posyandu dalam Pengolahan Makanan Pendamping Air Susu Ibu bagi Bayi Usia 6-24 Bulan - Rizkia Amilia; Nurul Qamariah Rista Andaruni; Indriyani Makmun; Ana Pujianti Harahap; Aulia Amini; Baiq Masdariah; Evi Diliana Rospia (Yayasan Ahmad Mansyur Nasirah, 2022)
Malnutrition in infants and children will cause growth and development disorders that if not overcome early can continue until adulthood. The age of 0-24 months is a period of rapid growth and development, so it is often termed as a golden period as well as a critical period. Nutrition improvement programs can increase the number of quality complementary foods for breast milk, so far it has been carried out, including the provision of complementary breast milk to infants and children aged 6-24 months from poor families. Local breast-feeding has had several positive impacts, including; Mothers are more understanding and more skilled in making complementary foods from local foodstuffs in accordance with local customs and socio-culture. The purpose of this service activity is to improve the knowledge and skills of mothers and posyandu cadres in processing local breast milk complementary foods correctly. The method of implementing activities is carried out by applying action research steps with stages of planning, action, observation and evaluation, as well as reflection. The result of the implementation of the service was that there was an increase in knowledge by 70% and the processing skills of complementary foods in breast milk by 90%. Conclusion There is an increase in the knowledge and skills of mothers and posyandu cadres about training in processing local complementary foods. This service suggestion is that it is necessary to develop training on the processing of local complementary foods with a more varied menu